The Role of Echocardiography in Neonates and Pediatric Patients on Extracorporeal Membrane Oxygenation - Bautista-Rodriguez, Carles; Sanchez-de-Toledo, Joan; Da Cruz, Eduardo M. (Frontiers in Pediatrics, 2018)
Indications for extracorporeal membrane oxygenation (ECMO) and extracorporeal cardiopulmonary resuscitation (ECPR) are expanding, and echocardiography is a tool of utmost importance to assess safety, effectiveness and readiness for circuit initiation and separation. Echocardiography is key to anticipating complications and improving outcomes. Understanding the patient's as well as the ECMO circuit's anatomy and physiology is crucial prior to any ECMO echocardiographic evaluation. It is also vital to acknowledge that the utility of echocardiography in ECMO patients is not limited to the evaluation of cardiac function, and that clinical decisions should not be made exclusively upon echocardiographic findings. Though echocardiography has specific indications and applications, it also has limitations, characterized as: prior to and during cannulation, throughout the ECMO run, upon separation and after separation from the circuit. The use of specific and consistent echocardiographic protocols for patients on ECMO is recommended.